(untitled) - Naisbitt, John (London, 1996)
This latest work by mega-best-selling author Naisbitt identifies eight Asian megatrends that are reshaping our world. The number eight, considered lucky in Asia, is significant here. Coming political, economic, and cultural changes will soon render Asia the dominant region of the world, and Naisbitt offers advice that will help the reader profit by the changes. The work looks at the region as a whole. In general, things Western are falling out of favor, as key places return to Chinese rule. However, Western problems such as divorce and crime are on the increase. The magnitude and far-reaching effects of the modernization of Asia are emphasized here; Naisbitt even asserts that the changes in modernization are without question the most important events taking place in the world today. Japan has just begun an economic decline that will increase rapidly in the coming years. The book does not linger long on any topic but gives readers snippets of information before moving on. A chart contrasts Asian and American values, shedding light on the respective cultures. Not surprisingly, Americans are said to value individual rights over an orderly society, which may explain the situation in which we currently find ourselves. Extensive notes are provided. Recommended for all public and academic libraries. (Index not seen.)-Lisa K. Miller, Paradise Valley Community Coll. Lib., Phoenix
Keywords: Economic forecasting,Asia; Economic conditions; 1945-; Asia